Identification of Adducin-Binding Residues on the Cytoplasmic Domain of Erythrocyte Membrane Protein, Band 3 - Franco, Taina (Biochem J, 2016)
Two major complexes form structural bridges that connect the erythrocyte membrane to its underlying spectrin-based cytoskeleton. Although the band 3-ankyrin bridge may account for most of the membrane-to-cytoskeleton interactions, the linkage between the cytoplasmic domain of band 3 (cdb3) and adducin has also been shown to be critical to membrane integrity. In this paper, we demonstrate that adducin, a major component of the spectrin-actin junctional complex, binds primarily to residues 246 through 264 of cdb3, and mutation of two exposed glutamic acid residues within this sequence completely abrogates both α- and β-adducin binding. Because these residues are located next to the ankyrin binding site on cdb3, it seems unlikely that band 3 can bind ankyrin and adducin concurrently, reducing the chances of an association between the ankyrin and junctional complexes that would significantly compromise erythrocyte membrane integrity. We also demonstrate the adducin binds the kidney isoform of cdb3, a spliceoform that lacks the first 65 amino acids of erythrocyte cdb3, including the central strand of a large beta-pleated sheet. Because kidney cdb3 is not known to bind any of the common peripheral protein partners of erythrocyte cdb3, including ankyrin, protein 4.1, glyceraldehyde-3-phosphate dehydrogenase, aldolase, and phosphofructokinase, retention of this affinity for adducin was unexpected.